You need only one bull to cover fifty cows: Zulu women and 'traditional' dress - Klopper, Sandra (My University, 1987)
This paper tries to place the contemporary dress of married Zulu women into a broad historical framework. It therefore addresses the the problem of why, despite radical economic and political transformations, some of the present conventions of female dress have remained virtually unchanged since Shakan times.(1) By looking particularly at the history of the institution of marriage, it attempts to demonstrate how the meanings ascribed to, but also the roles of these conventions have been affected by the codification of so-called customary law and the growth of migrant labour. Given the paucity of information on past perceptions and interpretations of female dress it must be pointed out, though, that many of the observations which follow are necessarily speculative.
African Studies Seminar series. Paper presented June 1987
Keywords: Clothing and dress. Social aspects. South Africa; Women, Zulu. Social life and customs; Married women. South Africa. KwaZulu-Natal; Leather garments. South Africa. KwaZulu-Natal; Clothing and dress. South Africa. KwaZulu-Natal; Women, Zulu. Clothing; Zulu (African people). Clothing. Social aspects